Sistem Informasi Pengorderan Barang - Susanti, Mira (Riset Sinergi Indonesia (RISINDO), 2023)
Technology changes civilization and human behavior globally such as social change so that ordering goods can also be done online. This can be done by several users who already have access rights. The existence of an ordering information sistem is expected to help produce accurate information about products in processing ordering goods. The method used in this study is the Sistem Development Life Cycle (SDLC) method which produces quality work stages that are in accordance with sistem objectives